Congenital pulmonary airway malformation and bronchopulmonary sequestration in infants – a rare diagnosis - Cachão, Joana (2021)
Herein is described the case of a two-month-old female infant with recurrent respiratory infections, admitted to the Pediatric Emergency Department with productive cough, respiratory distress, and fever. Chest radiography showed an heterogenous hypotransparent image in the left pulmonary field and contralateral deviation of the mediastinum. Angiotomography revealed bilateral bronchopulmonary sequestration and a systemic vessel contributing to area irrigation. The patient was submitted to vessel occlusion and lacquering, left inferior lobectomy, and resection of a right lower lobe segment. Histological examination confirmed intralobar bronchopulmonary sequestration and type 2 congenital pulmonary airway malformation in the left lung, and extralobar bronchopulmonary sequestration in the right lung. With this report, the authors intend to emphasize the importance of clinical suspicion of congenital anomalies in infants with recurrent respiratory infections.